Optimum Permanent Magnets Configuration in Flat-Quasi Linear Permanent Magnet Generators - Fransisco Danang Wijaya; Budi Azhari; Harnoko Stephanus (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Flat-quasi type of linear permanent magnet generators (LPMGs) have been considered to be applied for several applications, such for wave energy conversion and free piston combustion engine. One of the important issues concerning LPMG is the permanent magnets configuration, due to its effects to the generator’s excitation performance. In this paper, a 1 kW flat-quasi LPMG would be designed and built. During the process, optimum permanent magnets configuration was required and researched. The optimum configuration considered the output power and resulted cogging force. Invetigation was then conducted by modifying several variables, including poles’ arrangement, pole length, number of pole, and pole skewing angle. The modification constraints were total permanent magnets’ volume and generator dimension. The results showed that permanent magnet configuration with halbach arrangement, pole length equals 55% of the slot pitch length, and 61.19o skewing angle produced the optimum output values.